Effects of Chloramphenicol on the Titer of Widal in Typhoid Fever - Hafni Z. Soesilo; Yati Soenarto; Soelistyowati Soelistyowati; Ristanto Ristanto; Ismangoen Ismangoen (Paediatrica Indonesiana, 1982)
A study was camled out on 93 cases of Typhuid fever admitted to the Department of Child Health, Gadjah Mada University Hospital in Yogyakarta.The diagnosis is based on the discovery of Salnwnella typhi in the blood.It is stated that Chloramphenicol pos3esses an immunosuppressive nature ruppressing the titer of antibodies.Chloramphenicol has been administered with a dosagre of 75 mg/kg bodywelght/day.Checking on the titer of Widal war done weekly, beginning with the first week (prior to treatment with Chloramphenicol), larting four weeks (up to approximaJelyone or two weeks after Chlorampheru'col administration was stopped).ln only 91 of 93 cases follow up war possible: the W.idal titer incrt!OSed in 29 cases (31.9%), decreased in 23 (25.i%) cases and was constant in 39 cases (42.9%).